2012
DOI: 10.1093/cid/cis1204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Matrix-Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry on the Clinical Management of Patients With Gram-negative Bacteremia: A Prospective Observational Study

Abstract: In a low prevalence area for extended spectrum betalactamases (ESBL) and multiresistant gram-negative bacteria, MALDI-TOF performed on blood culture pellets had an impact on the clinical management of 35.1% of all gram-negative bacteremia cases, demonstrating a greater impact than Gram stain reporting. Thus, MALDI-TOF could become a vital second step beside Gram stain in guiding the empirical treatment of patients with bloodstream infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
139
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(149 citation statements)
references
References 21 publications
(28 reference statements)
6
139
1
3
Order By: Relevance
“…By testing of positive blood culture bottles using MALDI-TOF MS, time to organism identification is reduced by a day or more (69 ). A limitation is that antimicrobial susceptibility is not provided.…”
Section: Testing Of Positive Blood Culture Bottlesmentioning
confidence: 99%
“…By testing of positive blood culture bottles using MALDI-TOF MS, time to organism identification is reduced by a day or more (69 ). A limitation is that antimicrobial susceptibility is not provided.…”
Section: Testing Of Positive Blood Culture Bottlesmentioning
confidence: 99%
“…The application of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) technology for the identification of microorganisms in clinical diagnostics has significantly improved the time it takes to obtain results. This is especially true for the use of MALDI-TOF MS in identifying pathogens in blood cultures (BCs), a procedure that has been well evaluated (9)(10)(11). However, with the emergence of multiresistant Gram-negative bacteria, valid prediction of susceptibility based on the species alone is no longer possible (12,13).…”
mentioning
confidence: 99%
“…This technology allows identification of both Gram-positive and Gramnegative bacteria (to a species level) within a few minutes, with a relatively low bacterial load being necessary for identification. A recent large observational study has demonstrated clinical benefit for this quick turn-around time [9]. In fact, we would even suggest that to have such a system, to accurately give us which organism is our pathogen and its sensitivity as a point-of-care test, is an obvious holy grail for intensivists.…”
Section: Editorialmentioning
confidence: 99%
“…Another area of intense research is to identify causative organisms more timeously [4,8,9]. One of the most promising techniques is matrix-assisted laser desorption ionization time-of-flight mass spectrometry or MALDI-TOF MS (sometimes without the MS).…”
Section: Editorialmentioning
confidence: 99%